Perancangan Sistem Informasi Berbasis Web Pada SMKS Ibrahimy Situbond - Arya Widi Pratama; Lukman Fakih Lidinillah (LKP Unity Academy, 2025)
This study aims to design and develop a web-based e-report information system as a solution to the manual grade management process at SMKS Ibrahimy Situbondo, which previously relied on Microsoft Excel. The system was developed using the Waterfall development method, consisting of requirement analysis, system design using DFD, ERD, CDM, and PDM, implementation with PHP and MySQL, Black Box Testing, and maintenance. The results indicate that the system successfully automates the processes of inputting, summarizing, and distributing grades, thereby improving the efficiency, accuracy, and transparency of academic data management while providing real-time access for teachers, class advisors, students, and parents. Future enhancements may include integrating a mobile application and analytics dashboard to expand functionality and improve accessibility.